2000
DOI: 10.1128/cdli.7.5.835-839.2000
|View full text |Cite
|
Sign up to set email alerts
|

An IS 711 Element Downstream of the bp26 Gene Is a Specific Marker of Brucella spp. Isolated from Marine Mammals

Abstract: DNA polymorphism of the bp26 gene, coding for a diagnostic protein antigen for brucellosis, was assessed by PCR and restriction fragment length polymorphism analysis using primers to amplify the bp26 gene with its flanking regions. Surprisingly, whereas PCR performed on DNA of the reference strains of the six recognized Brucella species produced a product of the expected size (1,029 bp), PCR performed on DNA of three representative strains from marine mammals (from a seal, a dolphin, and a porpoise) produced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 25 publications
1
58
0
4
Order By: Relevance
“…DNA template was added to a PCR reaction mix containing HotStar TaqMaster Mix (Qiagen) primers targeting the Brucella-specific bp26 gene and downstream IS711 element (Cloeckaert et al, 2000). In addition to the sample templates, positive and negative controls were included.…”
Section: Tissue and Swab Analysismentioning
confidence: 99%
“…DNA template was added to a PCR reaction mix containing HotStar TaqMaster Mix (Qiagen) primers targeting the Brucella-specific bp26 gene and downstream IS711 element (Cloeckaert et al, 2000). In addition to the sample templates, positive and negative controls were included.…”
Section: Tissue and Swab Analysismentioning
confidence: 99%
“…PCR amplification of an IS711 element downstream of the bp 26 gene (Cloeckaert et al, 2000) confirmed isolates originating from the lungworms and kidney of the harbor porpoise possess the specific marker of Brucella spp. unique to isolations from marine mammals.…”
Section: Molecular Detection and Characterizationmentioning
confidence: 99%
“…Brucella has been reported to cause abortion in bottlenose dolphins (Tursiops truncatus) in the USA (Ewalt et al, 1994;Miller et al, 1999). Studies using molecular techniques have shown isolates differ from the six recognized species originating from terrestrial mammals (Cloeckaert et al, 2001). Phenotypically, these strains can be differentiated with respect to their requirement for increased carbon dioxide (CO 2 ) for primary growth; generally isolates originating from pinnipeds require increased CO 2 whereas isolates from cetaceans do not.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations